Use of the multiplier method to estimate the size of populations most at risk of human immunodeficiency virus infection in China: a systematic review. (August 2020) - Jing, L.W.; Cui, Y.H.; Yu, H.M.
Abstract: Objective: United Nations Programme on human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome and World Health Organization believe that some of the benchmark numbers collected may be inaccurate when using the multiplier method to estimate the size of populations most at risk of acquiring HIV. Here, study data have been evaluated to characterize the inaccurate benchmark numbers. Study design: The study design used is a systematic review. Methods: Studies published from 1 January 2004 to 1 December 2019 using the multiplier method to estimate the population proportions of men who have sex with men (MSM) and female sex workers (FSWs) in China were reviewed. Five electronic bibliographic databases were searched: Medline, the China National Knowledge Infrastructure, VIP Database for Chinese Technical Periodicals, Wanfang Data, and the Chinese BioMedical Literature Database. Results: In all eight studies of FSW, six of the estimated population proportions fell within the range of national estimates. However, the estimated MSM population proportions of all 18 studies fell outside the range of national estimates. Conclusions: When estimating the MSM population, the use of benchmark numbers from homosexual websites or MSM-frequented sites usually led to an inaccurate estimation. Therefore, benchmark numbers from services/programs that meet fundamental needs, such as those dealing with health and wellness, should be used. Highlights: Some of the benchmark numbers collected are inaccurate when using the multiplier method to estimate MSM population size Accurate population identification was seen to be key to avoiding an inaccurate benchmark number The benchmark data from services or programs that meet fundamental needs should be used to estimate MSM population size